BioactiveMarkers Based Pharmacokinetic Evaluation of Extracts of a TraditionalMedicinal Plant, Piper sarmentosum - Hussain, Khalid; Ismail, Zhari; Sadikun, Amirin; Ibrahim, Pazillah (Hindawi Publishing Corporation, 2011)
In vitro assays are economical and easy to perform but to establish relevance of their results to real clinical outcome in animals or human, pharmacokinetics is prerequisite. Despite various in vitro pharmacological activities of extracts of Piper sarmentosum, there is no report of pharmacokinetics. Therefore, the present study aimed to evaluate ethanol extract of fruit of the plant in dose of 500 mg kg−1 orally for pharmacokinetics. Sprague-Dawley rats were randomly divided into groups 1, 2, and 3 (each n = 6) to study absorption, distribution and excretion, respectively. High performance liquid chromatography (HPLC) with ultraviolet detection was applied to quantify pellitorine, sarmentine and sarmentosine in plasma, tissues, feces and urine to calculate pharmacokinetic parameters. Pellitorine exhibited maximum plasma concentration (Cmax) 34.77 ngmL−1± 1.040, time to achieve Cmax (Tmax) 8h, mean resident time (MRT) 26.00 ± 0.149 h and half life (t1/2) 18.64 ± 1.65 h. Sarmentine showed Cmax 191.50 ± 12.69 ng mL−1, Tmax 6 h, MRT 11.12 ± 0.44 h and t1/2 10.30 ± 1.98 h. Sarmentosine exhibited zero oral bioavailability because it was neither detected in plasma nor in tissues, and in urine. Pellitorine was found to be distributed in intestinal wall, liver, lungs, kidney, and heart, whereas sarmentine was found only in intestinal wall and heart. The cumulative excretion of pellitorine, sarmentine and sarmentosine in feces in 72 h was 0.0773, 0.976, and 0.438 μg, respectively. This study shows that pellitorine and sarmentine have good oral bioavailability while sarmentosine is not absorbed from the gastrointestinal tract.